OPTIMISATION OF WIND-RESISTANCE CABLE CONFIGURATIONS TO MINIMISE STRUCTURAL DEFORMATION IN SUSPENSION BRIDGE - Annisaturrahmah; Ade Yuniati Pratiwi (Jurnal Jalan Jembatan, 2026)
Stability and structural rigidity are critical challenges in suspension bridge construction due to inherent flexibility under dynamic wind and traffic loads. While Wind-Resistance Cable systems are recognised solutions, their efficiency depends heavily on precise geometric installation. This study addresses the scientific gap regarding the optimal placement and inclination angles specifically for the Cemara Ujung – Sungai Andai Suspension Bridge, as existing designs often lack site-specific geometric optimisation. Following FHWA-HRT-14-070 guidelines, numerical simulations using the Finite Element Method (FEM) were conducted via MIDAS Civil 2025. A parametric study tested three placement variations (FKP, DIN, HMR) and three inclination angles (0°, -45°, -54.7°). The existing bridge exhibits vertical deformation of -252.84 mm and lateral deformation of 16.93 mm. Analysis shows that geometric configurations significantly influence stiffness. The DIN configuration at a -45° inclination angle was identified as the optimal design, reducing vertical deformation by 9.46% (to -228.91 mm) and lateral deformation by 12.44% (to 15.06 mm). These findings suggest that positioning cables near supports at moderate angles provides the most effective contribution to controlling complex deformations. This research contributes valuable technical insights into optimising bridge stability through strategic cable geometry, bridging the gap between general wind-resistance theories and practical structural application for flexible suspension spans.   Keywords: Suspension Bridge, Wind-Resistance Cable, Pedestrian Bridge, Light Vehicular Bridge, Structural Deformation